UNICEF's Role in CPAP 2018-2022 To Combat Child Trafficking in India - Megahnanda Alidyan Kresnawati; Faradillah Isnaeni Putri (Future Science, 2022)
Child trafficking is the recruitment, transportation, smuggling, transfer, and receipt of children to exploit them through deception, violence, and coercion. Child trafficking is a violation of the rights and welfare of children, as well as denying them the opportunity to reach their full potential during their lifetime. International organizations exist to serve the needs of a nation with a specific issue. UNICEF is an international organization that focuses on upholding the rights of children around the world, especially those unfortunate enough to experience violence, discrimination, disease, and poverty. By presenting a 5-year program, the Country Programme Action Plan (CPAP) 2018-2022, UNICEF is here to solve the problem of child trafficking in India.